Determinants of organizational performance of football clubs - N. A. Osokin (Стратегические решения и риск-менеджмент)
Russian football currently finds itself in a challenging economic situation. In light of the upcoming FIFA World Cup in 2018 all members of the Russian football industry will be under immense pressure. Russian professional football clubs have been struggling to keep with European club management standards. This article aims to evaluate the industry-specific features of organizational performance within the context of professional football clubs. The current performance measurement system within Russian football is based on 5 straightforward licensing criteria, which do not conform with international requirements. During the course of the study the author was able to identify the main factors, which may be used to form a new performance measurement system for Russian professional football clubs.The findings of this paper allow to formulate the main directions of future research in the field of organizational performance of football clubs. The most acclaimed methodologies of foreign researchers attempted to combine both sporting and non-sporting (financial, marketing, etc.) indicators. The main theoretical findings may be used to modernize the current licensing system within Russian professional football. This article attempted to systemize the body of literature on organizational performance of sports organizations and football clubs by both Russian and foreign scholars. The conclusions of this study help broaden the understanding that in the current economic realities the ability to win competitions may not be regarded as the sole purpose of professional football clubs. Football clubs must strive to simultaneously achieve success on and off the pitch.